EDUKASI DAN PENDAMPINGAN SERTIFIKAT HALAL SELF DECLARE PRODUK RENGGINANG UMKM DESA BANTARSARI - Muhammad Hassan Muazis; Iqbal Ludy Abdullah; M. Adamsyah; Rismaya Anggun Nurlita; Uun Thoyibatul Khikma; Wiwit Tazkiyatun Nufus; Yudha Darmansyah (STIT Sirojul Falah Bogor, 2025)
Certification education is an effort to increase business actors' knowledge about halal products. MSME actors are given an understanding of the product halal certification process. Halal certification is a series of processes that must be passed by business actors, both individuals and business entities in the form of legal entities or not legal entities to obtain halal certificates. Halal certificates are obtained through several stages of examination to prove that the raw materials, production process, and product halal assurance system at a company are in accordance with the standards set by LPPOM MUI. According to Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises, it emphasizes that micro, small and medium enterprises (MSMEs) are productive economic businesses. Indonesia requires halal certification since October 17, 2019 with a maximum timeline of October 17, 2024 for food and beverage products. this means that after that date food products that do not have halal certification are prohibited from being traded. there are more than 7 MSMEs in bantarsari village, rancabungur subdistrict, bogor regency and the potential for business development. the types of businesses are generally micro, small and medium enterprises, including rengginang, renggining, guava sponge, guava dodol, banana chips, cassava chips, pickled guava and others. The target of this MSME is generally residents of RT. 005/006 and the people of bantarsari village.